An Economic Formulation to Elaborate Resistant Technical Porcelains Using Abundant Raw Materials: Thermal and Rheological Properties Characterization. Issue 4 (2nd October 2021) - Kitouni, Saida
Abstract : The aim of the current work is to investigate selected thermal and rheological properties of porcelains. Dilatometry and shrinkage were investigated in order to clarify the thermal porcelain behavior. Densification behavior indicated that specimen sintered at 1200°C for 2 h with a heating rate of 5°C.min –1 has firing shrinkage ratio of about 11.38%. This value is fairly accurate for the usual porcelain products (12.00%). Development of thermal expansion coefficient of those samples without calcination and calcined at the temperature range of 32°-1000°C with heating rate of 5°C.min –1 in air atmosphere has also been investigated. In other way, it has been found that NaCl addition was effective to bring down the porcelain slurries viscosity. Suspensions with concentrations of 1, 2 and 3 mass% have been prepared. It has also been found that NaCl addition was effective to decrease the viscosity of porcelain slurries. GRAPHICAL ABSTRACT: UF0001